Studi Konstruktivistik: Islam di Andalusia (Periode Masuk hingga Terusir) - Fikri Maulyda (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
This study examines the history of Islam in Andalusia from its arrival in the 8th century to its eventual expulsion in the 15th century, using a constructivist approach to analyze the socio-political and cultural transformations during this period. The research highlights how Islamic civilization interacted with existing Visigoth and Roman traditions, creating a unique synthesis that significantly influenced Europe. The qualitative descriptive method and content analysis of historical literature, archaeological studies, and ancient manuscripts were employed to reconstruct the history of Islamic Andalusia. The findings reveal six distinct phases of Islamic rule, marked by intellectual flourishing, political fragmentation, and eventual decline due to internal conflicts and external pressures. The study underscores the lasting impact of Andalusia's Islamic legacy on European Renaissance and modern civilization.